Research on Fish Diseases along Coastal Waters in China Based on Web GIS Database - Shengju Han; Youyou Wang; Shangyu Nie (2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology, 2011)
As China continues to develop economically, the challenges facing the country in regards to the management of its natural resources will continue to grow. China has always relied on the aquatic environment as an important source of protein, both through aquaculture and the development of tools that can disseminate information on environmental quality to both resource managers and the general public. This research reports on the development of information regarding the spatial distribution of important fish diseases across China. The architecture of this system and its intended application will be presented, along with a discussion of the challenge associated with the development of these systems in China.